GOLD INVESTMENT DECISIONS: FINANCIAL BEHAVIOR, GOLD PRICE AND INCOME AS MODERATING VARIABLE IN MEMBERS OF THE INDONESIAN AIR FORCE - Sri Lestari Yuli Prastyatini; Sekar Wijayanti Kusumaningrum (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Investment decisions can be influenced by various factors. This research aims to answer the main question whether financial behavior and gold price influence gold investment decisions with income as a moderating variable. This research position took place in Yogyakarta with total of 2400 respondents members of the Indonesian Air Force. The sample in this study was 96 respondents taken using a random sampling technique. Meanwhile, the data collection method uses a questionnaire via google form. The data analysis used was multiple linear regression and hypothesis using the SPSS 29. The research results show that financial behavior has a positive influence and gold prices has a negative influence on gold investment decisions. Meanwhile, income is not able to moderate the relationship between financial behavior and gold prices on gold investment decisions.